2022
DOI: 10.1002/elps.202100290
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new ultra‐high‐performance liquid chromatography–tandem mass spectrometry method for the determination of digoxin and digitoxin in plasma: Comparison with a clinical immunoassay

Abstract: Cardiac glycosides digoxin and digitoxin are used in therapy for the treatment of congestive heart failure. Moreover, these compounds can be responsible for intoxication cases caused by fortuitous ingestion of leaves of Digitalis. Due to the narrow therapeutic range of these drugs, therapeutic drug monitoring is recommended in the clinical practice. In this context, immunoassays‐based methods are generally employed but digoxin‐ and digitoxin‐like compounds can interfere with the analysis. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Nevertheless, digoxin immunoassays still overestimate digoxin concentrations compared with LC-MS/MS. Recently, Bollotari reported an average of 0.18 ng/mL positive bias with immunoassay compared with LC-MS/ MS. 52 In contrast, an older study indicated significant discordance between values obtained by an immunoassay and a more specific chromatography-based method in more than 20% of all specimens analyzed by authors. 53 Therefore, newer immunoassays are significant, more specific, and superior compared with older immunoassays.…”
Section: Gap Analysismentioning
confidence: 93%
“…Nevertheless, digoxin immunoassays still overestimate digoxin concentrations compared with LC-MS/MS. Recently, Bollotari reported an average of 0.18 ng/mL positive bias with immunoassay compared with LC-MS/ MS. 52 In contrast, an older study indicated significant discordance between values obtained by an immunoassay and a more specific chromatography-based method in more than 20% of all specimens analyzed by authors. 53 Therefore, newer immunoassays are significant, more specific, and superior compared with older immunoassays.…”
Section: Gap Analysismentioning
confidence: 93%
“…Methods for detecting digoxin concentration in blood mainly include HPLC, 20 capillary electrophoresis, LC-MS, and immunoassays including radioimmunoassay, enzyme immunoassay, fluorescence immunoassay, and chemiluminescence immunoassay. 21 Some of them are summarized as Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…ATTO520-C2-maleimide was obtained from ATTO-TEC (Siegen, Germany) and TAMRA-C5-maleimide was obtained from Biotium (Hayward, CA, USA). Other reagents, if not specified, were purchased from Sigma-Aldrich, Shanghai Sango Biotechnology, and Beijing Solarbio Biotechnology Co. Ltd. fluorescence polarization technology and competitive binding of antigen/antibody 2 ng/mL convenient, fast but limited to the small molecules, low sensitivity, and specific antibodies required DNA-based digoxin detection 27 changes in the equilibrium of the DNA strand displacement competition response 7.8 μg/ mL convenient but low concentrations of digoxin need to be detected over longer time lateral flow immunoassay with multicolor gold nanorod etching 28 the sample acts through a capillary tube and is visually detected with a colorimetric index bound to the antibody not reported convenient, fast but samples require additional processing steps and can only be semiquantitative HPLC-tandem mass spectrometry 20 ionizing components of the substance, the mass-to-charge ratio of the ions generated by different components, and qualitatively analyzed 0.5 ng/ mL highly sensitive but the equipment and reagent are expensive; highly skilled operator is needed Q-body technology (this study) detection based on the photoinduced electron transfer between fluorescent dye and tryptophan of antibody 0.023 ng/ mL convenient, fast and highly sensitive; preparation of recombinant antibody and labeling are needed…”
Section: Materials E Coli Competent Dh5α Cells For Gene Cloning and P...mentioning
confidence: 99%
“…The results indicated that over 50% of hospitals performed TDM for valproate sodium, digoxin, carbamazepine, vancomycin and cyclosporine. Of note, most of these drugs have narrow therapeutic ranges and high intra-and inter-individual variability (Patsalos et al, 2018;He et al, 2020;Deprez and Stove, 2021;Ballotari et al, 2022). In these scenarios, TDM is useful to adjust medication dosages of treatments to maximize clinical effectiveness and decrease their toxicity.…”
Section: Analysis For Implementing Projects Of Tdm and Pgx Testingmentioning
confidence: 99%